PENGARUH STRATEGI STORYTELLING DAN DISKUSI KELOMPOK BERBASIS PROGRESIVISME TERHADAP PERKEMBANGAN BAHASA SISWA SEKOLAH DASAR - Safitri, Sanseni; Maitris Yulida; Yeni Karneli; Zelhendri Zen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the differential effectiveness of storytelling and group discussion learning strategies, grounded in progressivism philosophy (Dewey, 1938), on the language development of fourth-grade elementary school students at SDN 21 Makalo, Sikakap District, Mentawai Islands Regency. The low literacy level of students in bilingual contexts motivated this research. A quasi-experimental pretest-posttest control group design was employed, involving 60 students divided into three groups: storytelling (n=20), group discussion (n=20), and conventional control (n=20). A validated 36-item language ability test covering phonological, morphological, syntactic, and pragmatic dimensions was used as the instrument (Cronbach's Alpha r=0.87). Interventions were conducted over eight weeks with 16 sessions per group. One-way ANOVA on gain scores revealed a significant inter-group difference (F(2,57)=18.43; p<0.001; η²=0.39, large effect). The storytelling group achieved the highest gain (M=24.5; SD=4.2; d=2.89), followed by group discussion (M=19.8; SD=3.7; d=2.34), and control (M=8.3; SD=3.1). Tukey HSD post-hoc tests confirmed significant pairwise differences across all groups (p<0.05). Storytelling most effectively enhanced syntactic competence (M=6.4), while group discussion produced lower pragmatic gains (M=4.6) due to code-switching tendencies in bilingual peer interactions. These findings affirm progressivism philosophy as a relevant theoretical foundation for language instruction and support the integration of structured storytelling alongside explicit language scaffolding in bilingual elementary school contexts.